Sepsis in Intensive Care Units (Research, Society and Development, 2022)
The Intensive Care Unit is a health care environment for critically ill patients in need of recovery and in need of support for their life functions. In this environment, patients are more vulnerable to nosocomial infection, consequently to sepsis. The main objective is to review the literature on sepsis in patients with traumatic brain injury, hospitalized in intensive care units. The methodology used was a literature review. Inclusion criteria were: articles between the years 2011 to 2022, written in Portuguese, English and Spanish, including case report, cohort, case control and randomized clinical trial studies. The exclusion criteria referred to those with a publication date prior to the year 2011, articles in languages ​​other than those mentioned above, incomplete texts and those that were not related to the topic. In view of this study, we can see the importance of assisting the patient to prevent the development of sepsis, as well as approaching it properly, in the effective application of protocols to promote prevention in improving their prognosis, evaluating the effect of interventions in reducing mortality of patients hospitalized for traumatic reasons.